OLIY TA’LIM TIZIMIDA “FUQAROLIK JAMIYATI” FANINI O’QITISHDA INNOVATSION TA’LIM TEXNOLOGIYALARIDAN FOYDALANISH - Sultonova Gulmira Mahmudovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
Today in Uzbekistan, in order to ensure the rule of law and the development of a truly democratic state and civil society, great attention is paid to improving the legal system and raising legal awareness and legal culture in society. From this point of view, one of the urgent tasks in raising the legal culture in society is the teaching of civil society in the higher education system. The article discusses the advantages and opportunities of using innovative educational technologies in the teaching of science in the educational process.